PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KEMAMPUAN MANAJEMEN TERHADAP MOTIVASI KERJA GURU BIMBINGAN DAN KONSELING DI SMA NEGERI SE-KOTA MEDAN - Edidon Hutasuhut (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
The objective of this research is to know the influence of transformational leadership of headmaster and principal's headmaster's ability to motivate teacher guidance and counseling in SMA Negeri Medan. The subjects of this study are guidance and counseling teachers with a total of 148 people. This research method is descriptive percentage. The results of this study indicate that the influence of transformational leadership of the principal on the motivation of teacher guidance and counseling work as Medan with significant level rhitung> rtabel (0,401> 0,161) and the influence of management ability to motivation of teacher guidance and counseling work as Medan Significant level rhitung> rtabel (0,261> 0,161). Keywords: Transformational Leadership, Management, Work                   Motivation